Photocatalytic Purification of Orange-II-Dye-Polluted Wastewater Using TiO2-Modified g-C3N4 Composite - Bin Guo; Monir Uzzaman; Mai Furukawa; Ikki Tateishi; Hideyuki Katsumata; Satoshi Kaneco (C)
Textile dyes are considered to be one of the major sources of water pollution due to their complex chemical structures. Photocatalytic dye degradation is an eco-friendly method that uses light-activated catalysts to break down complex dye molecules in wastewater into harmless byproducts. In the present study, pure and N-doped g-C3N4 were synthesized using one-pot calcination. The fabrication of g-C3N4/TiO2 and TC-g-C3N4/TiO2 was accomplished by physical mixing. The prepared photocatalysts were used to treat the Orange-II-polluted wastewater. The structural properties, surface morphology, light-harvesting capability, and electrochemical properties were assessed using XRD, XPS, SEM, TEM, BET, DRS, PL, EIS, Mott–Schottky, and transient photocurrent response (TPCR) analyses. The improved charge separation and migration properties of g-C3N4/TiO2 were confirmed by the PL, EIS, and TPCR results. TEM and XPS data confirmed the formation of a g-C3N4/TiO2 composite. Enhanced photocatalytic decolorization was achieved for g-C3N4/TiO2 compared with pure g-C3N4 or TiO2. The 1 wt% g-C3N4/TiO2 composite exhibited the highest (92.1%) decolorization efficiency during 60 min of UV irradiation. Furthermore, the pseudo-first-order reaction rate constant (k) of 1 wt% g-C3N4/TiO2 was calculated to be 0.0213 min−1, which was 2.5 times better than that obtained with bare TiO2. Finally, for a better understanding of the g-C3N4/TiO2 decolorization process, a possible reaction mechanism was proposed.